Assessment of mitral valve geometry for personalised annuloplasty ring development - Srisook, Chirattikan (2024)
Heart valve disease can occur when one valve or a combination of the heart valves is not working properly. Heart valve disease is found in more than one million people in the UK (Malhotra, 2012) and more than five million people in the USA each year (Nkomo et al., 2006). In terms of all types of heart valve disease, mitral regurgitation is the most common (Malhotra, 2012; Moore et al., 2016). Mitral valve repair, the preferred method for treating mitral regurgitation, typically requires surgical intervention. While mitral valve replacement is available, mitral valve repair is claimed to have better outcomes (Magne et al., 2008; Fattouch et al., 2009). Previous papers have shown that valve repair with the use of an annuloplasty ring is able to restore the valve functions and overcome the mitral regurgitation by reducing the mitral valve size to completely coapt the mitral orifice area.